Editorial: Towards 2030: Sustainable Development Goal 9: Industry, Innovation and Infrastructure. A Sociological Perspective - Andrzej Klimczuk; Grzegorz Piotr Gawron; Magdalena Klimczuk-Kochańska; Piotr Toczyski (Frontiers in Sociology, 2024)
This Research Topic explores the ninth Sustainable Development Goal (SDG), which aims to build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation, particularly in the context of post-COVID-19 pandemic recovery. The pandemic significantly impacted the manufacturing sector, leading to a global production drop, job losses, and disrupted supply chains, with less technology-intensive industries taking longer to regain ground. Despite these challenges, the United Nations highlights opportunities to enhance industrialization and technology distribution, emphasizing, among other things, the need to expand mobile broadband networks, increase research and development investment, and improve rural road connectivity.
Keywords: F64; O44; P48; Q55; L52; O38; 330; SDG9; environmental regulation; industrial policies; innovation; sustainable industrial development; technology transfer